2017
DOI: 10.1097/ccm.0000000000002206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Alternative Resuscitation Strategies, Host Response and Injury Biomarkers, and Outcome in Septic Shock: Analysis of the Protocol-Based Care for Early Septic Shock Study

Abstract: Objective The Protocol-based Care for Early Septic Shock (ProCESS) trial found no differences across alternative resuscitation strategies in all-cause mortality. A separate aim was to determine whether differences in resuscitation strategies affected trajectories of biomarkers of key pathways associated with downstream clinical outcomes of sepsis and whether there were differences in survival across treatment arms for patients with different baseline biomarker profiles. Design Secondary analysis of a large r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…The resultant reduction in the mean systemic pressure and relative hypovolemic state, paired with decreased systemic vascular resistance, results in hypotension 8. Prompt resuscitation of the circulation with administration of intravenous fluids is a key component of sepsis management 104105106. However, excessive administration and accumulation of fluids in an attempt to treat hypotension or oliguria after AKI is common and harmful.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant reduction in the mean systemic pressure and relative hypovolemic state, paired with decreased systemic vascular resistance, results in hypotension 8. Prompt resuscitation of the circulation with administration of intravenous fluids is a key component of sepsis management 104105106. However, excessive administration and accumulation of fluids in an attempt to treat hypotension or oliguria after AKI is common and harmful.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…Recent studies have shown that protocolized resuscitation strategies did not improved outcomes, but a minimal degree of resuscitation is needed to mitigate the risk of adverse outcomes. Finally, clear evidence shows that in addition to the risks of under-resuscitation, in the setting of AKI, volume overload from aggressive over-resuscitation is also harmful, creating a J or U shaped curve for resuscitation and mortality 104105106114…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…While these mechanisms may be distinct in animal models, they appear to be more complex and interrelated in clinical practice and sorting out causality is difficult. Inflammatory mediator levels vary widely (eg IL-6 can range from <10 to >1 million pg/ml in sepsis 96 ) and extracorporeal blood purification may fail to significantly modulate their plasma levels. Based on the current findings about different pathways linking kidney injury with distant organs, therapeutic strategies that target just a single molecule are less likely to succeed in reducing the AKI-induced distant organ dysfunctions.…”
Section: Clinical Practice and Future Researchmentioning
confidence: 99%
“…95 Applying blood purification to all patients may be beneficial for some and have no effect or even be injurious to others (eg by removal of various antioxidants, micronutrients, electrolytes, antibiotics and other medications essential for optimal organ function and recovery during the process). Inflammatory mediator levels vary widely (eg IL-6 can range from <10 to >1 million pg/ml in sepsis 96 ) and extracorporeal blood purification may fail to significantly modulate their plasma levels. 97 Future investigations will need to evaluate whether a personalized approach that links the use of extracorporeal blood purification techniques to mediator levels and matches micronutrients, antibiotic and electrolyte loss to blood purification intensity improves outcomes in these patients.…”
Section: Clinical Practice and Future Researchmentioning
confidence: 99%
“…It is not known if EGDT further increases mortality compared with sick controls without EGDT due to effect heterogeneity that is determined by disease severity (Figure 1). In order to test EGDT for effect modification and treatment interactions, survival outcomes in the Protocolized Care for Early Septic Shock (ProCESS) trial were analyzed in relation to inflammatory, coagulation, oxidative stress, and tissue hypoxia biomarkers measured in patients enrolled (19). Whereas protocol-based resuscitation had no effects on baseline coagulation, oxidative stress, and tissue hypoxia biomarkers, patients with lower baseline concentrations of inflammatory biomarkers seemed to benefit from it.…”
Section: Editorialmentioning
confidence: 99%